The predictors for high-quality embryos for advanced age women undergoing intracytoplasmic sperm injection cycles in Hospital USM Fertility Unit - Hafizi, Ezanaton Nisar Omar (2022)
Advanced age women associated with fertility decline as a result of ovarian reserve depletion and declining oocyte and embryo quality. Determining the predictor factor of oocytes and embryo quality may assist in stimulation target and cycle prediction. The study is to determine the oocyte and embryo quality among advanced age woman receiving Intracytoplasmic Sperm Injection cycles in Hospital USM Fertility Unit. Predictors for highquality oocytes and embryos were identified. This prospective observational study was performed over a period of 24 months in Hospital USM Fertility Unit, on 941 oocytes retrieved from 124 women of advanced age receiving ICSI. Oocytes grading by means of its morphological appearances and the SARTCORS grading system for embryo grading were used to determine their qualities. Fertilization rate and cleavage rate were expressed as percentage per cycle, while pregnancy rate was expressed as percentage per transfer. Possible predictors of good-quality oocytes and high-quality embryos were evaluated using single and multiple regression tests, with p < 0.05 considered as significant. From 941 retrieved oocytes, 291 oocytes (39.64%, mean 2.35 SD=1.79 per cycle) were Grade 1 oocytes, while 272 oocytes (37.06%, mean 2.19 SD=1.27) were Grade 2 oocytes and the rest (n=171, 23.30% mean 1.38 SD=1.22) were Grade 3 oocytes. Among 586 available embryos, 500 (85.32%, mean 4.03 SD=3.22) high-quality embryos were obtained. The fertilization and cleavage rates were 81.6% and 97.8%, per cycle respectively. Seventy-six embryo transfers were conducted, with 17 successful conceptions (pregnancy rate = 22.37% per transfer). There were no miscarriages among the pregnancies. This study has proved that increasing the number of collecting mature oocytes and cleavage rate could increase the chance of obtaining high-grade embryos. This could increase the success of ICSI among women of advanced age. Therefore, efforts to find ways to increase oocytes quantity and quality among advanced aged women must be made.